Global Trends in Digital Entrepreneurship Research Based on Bibliometric Analysis of the Scopus Database from 2013 to 2023 - Loso Judijanto (West Science Journal Economic and Entrepreneurship, 2026)
The rapid advancement of digital technologies has significantly transformed entrepreneurial activities and business ecosystems worldwide. This study aims to analyze global research trends in digital entrepreneurship through a bibliometric approach using publications indexed in the Scopus database from 2013 to 2023. The study employs bibliometric analysis and network visualization using VOSviewer to examine publication patterns, collaboration networks among authors, institutions, and countries, as well as the thematic structure of the research field. The results show a significant growth in scholarly publications on digital entrepreneurship over the past decade, indicating increasing academic interest in the topic. The collaboration analysis reveals that several countries, particularly the United States, the United Kingdom, Germany, and the Russian Federation, play central roles in international research networks. In addition, the co-authorship and institutional networks highlight the presence of influential scholars and universities that actively contribute to the development of digital entrepreneurship studies. Keyword co-occurrence analysis identifies major research themes such as entrepreneurship, digital technologies, digital economy, business models, and digital innovation, while emerging topics such as sustainability, startups, and digitalization indicate evolving research directions. The findings demonstrate that digital entrepreneurship has developed into a dynamic and interdisciplinary research area that integrates perspectives from entrepreneurship, information systems, and innovation studies. This study provides a comprehensive mapping of the intellectual structure of digital entrepreneurship research and offers insights into future research opportunities in the evolving digital economy.